FOOD-ENERGY PRICE DYNAMICS: ANALISIS PENGARUH FLUKTUASI HARGA KOMODITAS PANGAN DAN HARGA ENERGI TERHADAP INFLASI DI INDONESIA 2014 – 2024 - Rr. Halimatu Hanna; Tiara Nirmala (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
Food, which is all-time good and energy which is a universal intermediary good, remain highly relevant for ongoing research and development. The primary essence of this study is to examine the short-term and long-term effects of rice prices, the world food price index, the transportation price index, the housing, water, electricity, and household fuel price index (IHPL), as well as Brent crude oil prices, on the consumer price index (CPI). The Autoregressive Distributed Lag (ARDL) method is employed to analyze the dynamic relationships among these variables. The data span ten years (January 2014 – December 2024) to depict prevailing economic phenomena. The findings reveal that, in the short term, IHPL and Brent oil prices are significant determinants of CPI movements in Indonesia. IHPL exhibits a dominant and complex influence, while Brent oil prices exert a significant impact with a one-period lag (lag 1). In contrast, rice prices, the world food price index, and the transportation price index show no significant effects on CPI in either the short or long term.